EFEKTIVITAS MODEL PEMBELAJARAN ROTATING TRIO EXCHANGE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII - Pakan, Nastupani; Munir, Nilam Permatasari (Math Educa Journal, 2021)
This study aims to determine the critical thingking skills of grade VIII students of MTs. Batusitanduk before and after the aplication of the Rotating Trio Exchange learning model were effective against the critical thinking skills of class VIII students of MTs. Batusitanduk. This type of research is a quasi-experimental research design that uses a one-group pre-test post-test design. The population in this study were students of class VIII MTs. Batusitanduk and the sample was class VIII.A which was taken from one class of four existing classes and totaled 34 students. The data collection instruments in this study were tests, observations, and documentation. The results showed students' critical thinking ability before applied RTE by 20.76 belongs to the category of low critical thinking ability, increased after applied RTE by 70.59 belongs to the category of high critical thinking ability, and hypothetical test results (t-test) obtained gis scores. (2-tailed) 0.000<0.05 then H0 is rejected and H1 is accepted meaning there is an average difference in critical thinking ability between pretest and posttest students. So, RTE learning model is effective against the critical thinking ability of grade VIII.A MTs.Batusitanduk students.